(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate a class of the fractional (p, q)-difference initial value problem with the fractional (p, q)-integral boundary conditions with the aid of the method of successive approximations(Picard method) and fractional (p, q)-Gronwall inequality, obtaining sufficient conditions for the existence, uniqueness and continuous dependence results of solutions.